Physically active patients with coronary artery disease : a longitudinal investigation of the processes of exercise behaviour change - Kanning, Martina (My University, 2010)
Objectives. Although regular exercise is important for patients with coronary artery disease (CAD), most CAD patients are not sufficiently active. The transtheoretical model offers a framework for the process of exercise behaviour change. But until today, it is not clear which processes of exercise behaviour change (POC) support CAD patients in maintaining exercise after discharge.
Design. A longitudinal study with baseline measure and 6-month follow-up has been conducted. German CAD patients were mailed at home after discharge. POC and exercise were self-reported.
Methods. A total of 204 CAD patients were selected from five rehabilitation centres. A total of 108 CAD patients, which were in the post-action stages, provided data at baseline and follow-up. Two different analyses were carried out. Firstly, structural equation modelling with baseline data (N =147) was used to test the hierarchical order of the POC in experiential and behavioural processes. Secondly, cross-lagged panel analysis was used to investigate whether POC lead to exercise or vice versa and which POC support CAD patients in maintaining exercise.
Results. Comparative analysis indicates that the two hierarchical-factor model fits the data significantly better than the one hierarchical-factor model (χ2diff(1)=19.04, p <.001), even though experiential and behavioural processes are highly correlated (r =.98, p <.001). Standardized effects of the antecedent cross-lags are significant for consciousness raising (β=0.27), reinforcement management (β=0.28), self-liberation (β=0.28), and stimulus control (β=0.33) indicating that these POC are predictive for CAD patients maintaining exercise.
Conclusion. Although some POC support the exercise behaviour change process and the hierarchical structure is apparent, it may be beneficial to adapt the POC to give a more precise understanding of the change processes.
Keywords: 796